A hardware-in-the-loop simulation facility for the attitude determination and control system of SUNSAT - Engelbrecht, J. A. A. (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.Ing) -- University of Stellenbosch, 1999.